2010
DOI: 10.1002/cncr.25445
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an hMSH3 defect in familial hamartomatous polyps

Abstract: BACKGROUND:Patients with hamartomatous polyposis syndromes have increased risk for colorectal cancer (CRC). Although progression of polyps to carcinoma is observed, pathogenic mechanisms remain unknown. The authors examined whether familial hamartomatous polyps harbor defects in DNA mismatch repair (MMR), and assayed for somatic mutation of PTEN, a gene inactivated in the germline of some hamartomatous polyposis syndrome patients. METHODS: Ten hamartomatous polyposis syndrome patients were genotyped for germli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…EMAST has been observed in a number of cancers, including small cell cancer of the lung (10), bladder cancer (11), ovarian cancers (9), and colorectal cancers (1215), and among benign familial hamartomatous polyps in the colon (25). EMAST is strongly associated with inflammation, and its presence is a biomarker for poor prognosis in patients with colorectal cancers (15,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…EMAST has been observed in a number of cancers, including small cell cancer of the lung (10), bladder cancer (11), ovarian cancers (9), and colorectal cancers (1215), and among benign familial hamartomatous polyps in the colon (25). EMAST is strongly associated with inflammation, and its presence is a biomarker for poor prognosis in patients with colorectal cancers (15,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of MSH2 and MLH1, the most common proteins affected in Lynch Syndrome, causes complete loss of MMR function; MLH1 is also the principal protein affected in sporadic MSI colorectal cancers [13]. When between 0% and 20% of markers show frameshifts, this is termed MSI-Low, and the frameshift is almost exclusively in the dinucleotide markers and not mononucleotide markers [1,10,11]. Although MSH6 dysfunction can generate mono- and di-nucleotide frameshifts, the absence of any mononucleotide frameshifts characteristic of MSI-Low is most likely associated with isolated MSH3 dysfunction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…When between 0% and 20% of markers show frameshifts, this is termed MSI-Low, and the frameshift is almost exclusively in the dinucleotide markers and not mononucleotide markers [1,10,11]. Although MSH6 dysfunction can generate mono- and di-nucleotide frameshifts, the absence of any mononucleotide frameshifts characteristic of MSI-Low is most likely associated with isolated MSH3 dysfunction [10,11]. Lack of any mono- or di-nucleotide markers with frameshifts defines microsatellite stable (MSS) CRCs, equating to no observable defect in MMR function [1,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Along a similar vein, others have found that a defect in DNA MMR, namely hMSH3 function can be associated with frameshift mutation of PTEN [46]. Loss of hMSH3 could occur in the setting of inflammation, a common finding within hamartomatous polyps, and inflammation has been associated with acquired DNA MMR defects [35,36].…”
Section: Is There a Genotype-phenotype Correlation?mentioning
confidence: 84%